Enhanced carbon dioxide causing the dust storm‐related increase in high‐altitude photoelectron fluxes at Mars. Issue 22 (19th November 2015) - Xu, Shaosui; Liemohn, Michael; Bougher, Stephen; Mitchell, David
Abstract: Several studies have shown that the Martian global dust storm occurred in 2001 had a long‐term influence on high‐altitude photoelectron fluxes by analyzing the observations of the magnetometer/electron reflectometer instrument on board Mars Global Surveyor, most likely because the dust altered the neutral atmosphere in a significant way in terms of photoelectron production and loss. This study investigates candidate atmospheres that can replicate observations, especially focusing on the role that thermospheric composition and density play in high‐altitude photoelectrons. Through the simulations of our SuperThermal Electron Transport model, it is found that high‐altitude photoelectron fluxes at more field‐aligned pitch angles are very sensitive to composition change and surprisingly independent of density. For more perpendicular pitch angles, both composition and density take part in determining photoelectron fluxes. Also, a CO2 atmosphere is the only one of the tested atmospheres that can qualitatively match the observation, which suggests that the global dust storm might have altered the photoelectron fluxes via causing CO2 to be the dominant species at a much larger altitude range than usual. Key Points: High‐altitude photoelectron fluxes are very sensitive to atmosphere composition change High‐altitude photoelectron is also independent of neutral density at PA ∼0 Global dust storm in 2001 probably caused CO2 dominating a larger altitude range